Performance evaluation of some elite cardamom landraces from the Cardamom Hill Reserve of Kerala - Hrideek T.K.; Radhakrishnan V.V; Mohanan K.V.; Raghu A.V. and Kuruvilla K.M
Even though about twelve improved cardamom varieties have been released in India, many of the farmers of the traditional cardamom tracts of the country use farmer selected landraces as planting material and hence the importance of such landraces is not questionable. A study has been carried out to assess the performance of ten elite landraces of cardamom collected from Idukki district of Kerala state of India namely Panikulangara-1, Panikulangara-2, Njallani, Vali green gold, Palakkudi, PNS Vaigai, Vander cardamom, Ela Rani-1, Ela Rani-2 and Ela Rani-3 using ICRI-2, an improved variety released by Indian Cardamom Research Institute as control. Observations on seven growth characters, nine yield characters and four quality characters were made and compared. The present findings indicate the potential of selecting genotypes like Ela Rani- 2, Ela Rani- 3, Palakkudi and Vali green gold for further trials and evaluation protocols so that varieties with significantly superior characters could be developed.